Pengaruh Leverage, Citra Perusahaan dan Sensitivitas Industri Terhadap Pengungkapan Corporate Social Responsibility Dimoderasi oleh Ukuran Perusahaan - Mahfudyanto, Akhirul; Ruhiyat, Endang; Holiawati, Holiawati (Universitas Pamulang, 2024)
This research aims to examine and analyze the influence of leverage, company image and industry sensitivity on corporate social responsibility disclosure moderated by company size in non-cyclical consumer companies listed on the Indonesia Stock Exchange for the period 2017 to 2022. This type of research is research with an associative quantitative approach. The population of this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange in the period 2017 to 2022. The sampling technique in this research is a purposive sampling technique with the results from 113 research populations becoming 34 research samples processed and 170 data processing. The data used is panel data obtained from secondary data collected using library and documentation methods. The data analysis method consists of descriptive statistical analysis, panel data regression and Moderated Regression Analysis (MRA) using Microsoft Excel and Eviews 10. The research results show that simultaneously leverage, company image and industry sensitivity influence corporate social responsibility disclosure. Meanwhile, partially, leverage and company image do not influence corporate social responsibility, but industry sensitivity influences corporate social responsibility disclosure. And environmental performance as a control variable influences corporate social responsibility disclosure in non-cyclical consumer companies listed on the Indonesia Stock Exchange in the period 2017 to 2022. Meanwhile, company size is unable to moderate the relationship between leverage and corporate social responsibility disclosure and the relationship between corporate image and corporate social responsibility disclosure, but company size can weaken the relationship between industry sensitivity towards disclosure of corporate social responsibility. This research can be used as material for consideration company decision making in contributing to the environment.